Effect of vanadium(IV) compounds in the treatment of diabetes: in vivo and in vitro studies with vanadyl sulfate and bis(maltolato)oxovandium(IV) - Willsky, G.R; Goldfine, A.B; Kostyniak, P.J; McNeill, J.H; Yang, L.Q; Khan, H.R; Crans, D.C (Journal of inorganic biochemistry, 2001)
Vanadyl sulfate (VOSO 4) was given orally to 16 subjects with type 2 diabetes mellitus for 6 weeks at a dose of 25, 50, or 100 mg vanadium (V) daily [Goldfine et al., Metabolism 49 (2000) 1–12]. Elemental V was determined by graphite furnace atomic absorption spectrometry (GFAAS). There was no correlation of V in serum with clinical response, determined by reduction of mean fasting blood glucose or increased insulin sensitivity during euglycemic clamp. To investigate the effect of administering a coordinated V, plasma glucose levels were determined in streptozotocin (STZ)-induced diabetic rats treated with the salt (VOSO 4) or the coordinated V compound bis(maltolato)oxovandium(IV) (abbreviated as VO(malto) 2) administered by intraperitoneal (i.p.) injection. There was no relationship of blood V concentration with plasma glucose levels in the animals treated with VOSO 4, similar to our human diabetic patients. However, with VO(malto) 2 treatment, animals with low plasma glucose tended to have high blood V. To determine if V binding to serum proteins could diminish biologically active serum V, binding of both VOSO 4 and VO(malto) 2 to human serum albumin (HSA), human apoTransferrin (apoHTf) and pig immunoglobulin (IgG) was studied with EPR spectroscopy. Both VOSO 4 and VO(malto) 2 bound to HSA and apoHTf forming different V-protein complexes, while neither V compound bound to the IgG. VOSO 4 and VO(malto) 2 showed differences when levels of plasma glucose and blood V in diabetic rodents were compared, and in the formation of V-protein complexes with abundant serum proteins. These data suggest that binding of V compounds to ligands in blood, such as proteins, may affect the available pool of V for biological effects.